Analisis Kepemimpinan Joko Widodo dalam Pengambilan Keputusan Strategis Pemindahan Ibu Kota Negara ke IKN - Vanesha Alexandria Darmawan; Sanesa Tri Andara; Asyfa Nurul Askia; Rival Rezano; Yulia Hanoselina (CV. ITTC INDONESIA, 2026)
National leadership in facing challenges of state governance transformation is a central issue in contemporary public administration and political science. The relocation of Indonesia's capital city from Jakarta to Ibu Kota Nusantara (IKN) in East Kalimantan represents one of the most significant strategic decisions in the modern history of Indonesian governance. This study aims to map academic literature on the role of Joko Widodo's leadership in the strategic decision-making process for capital relocation, identify existing research gaps, and formulate a future research agenda. The study employs transformational leadership theory, originally introduced by Burns (1978) and further developed by Bass (1985) through its four dimensions (4I), in conjunction with Mintzberg et al.'s (1976) strategic decision-making framework. A Systematic Literature Review (SLR) method based on PRISMA was applied, with data collected through systematic searches of Scopus, Sinta, and Google Scholar databases yielding 10 scientific articles published between 2020 and 2026. Findings reveal that Joko Widodo's transformational leadership played a dominant role in advancing the IKN policy through his capacity to build long-term vision, consolidate political coalitions via a reciprocity game model, and make timely decisions in complex situations. However, the analysis also identifies significant limitations in public participation, decision-making transparency, and institutional accountability, which affect the overall democratic legitimacy of the IKN policy.